1993
DOI: 10.1002/1097-4679(199311)49:6<891::aid-jclp2270490617>3.0.co;2-8
|View full text |Cite
|
Sign up to set email alerts
|

The stability of WAIS-R IQ for 16-year-old students retested after 3 and 8 months

Abstract: The stability of Wechsler Adult Intelligence Scale‐Revised IQs was investigated for 52 students 16 years of age. Half of the subjects were retested after a 3‐month interval; half after an 18‐month interval. Stability coefficients were uniformly high for both retest intervals. Gains in Verbal, Performance, and Full Scale IQ over 3 months were similar to practice effects reported for adult subjects. However, IQs for males retested after 18 months increased beyond the practice effect. Females retested after 18 mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

1995
1995
2006
2006

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…Concordantly, there is a consistent lack of significant association between frontal-lobe measures and IQ scores in children (Holzman et al 1983, Siegel 1988, Dennis et al 1991, Welsh et al 1991 and adults (Stuss et al 1983, Warrington et al 1986). Moreover, while IQ would be expected to remain stable throughout the lifespan (Mortensen and Klevens 1993, Thompson and Molly 1993, Haddad et al 1994, it is not necessarily the case that the mnemonic and other problem-solving impairments noted here will persist.…”
Section: Discussionmentioning
confidence: 99%
“…Concordantly, there is a consistent lack of significant association between frontal-lobe measures and IQ scores in children (Holzman et al 1983, Siegel 1988, Dennis et al 1991, Welsh et al 1991 and adults (Stuss et al 1983, Warrington et al 1986). Moreover, while IQ would be expected to remain stable throughout the lifespan (Mortensen and Klevens 1993, Thompson and Molly 1993, Haddad et al 1994, it is not necessarily the case that the mnemonic and other problem-solving impairments noted here will persist.…”
Section: Discussionmentioning
confidence: 99%
“…To be consistent, we converted the raw scores from sub-tests to scaled score equivalents using the corresponding norms for the ages of 16–17 years. The subscales of Similarities, Digit Span, Digit Symbols and Block Design that were used in this study are suitable for emotionally disturbed patients, and their scaled scores do not differ from those of the Wechsler Intelligence Scale for Children [28,29]. A Logical Prose Subtest, Story recall A, from the Wechsler Memory Scale WMS; [30] was used as a measure of immediate and delayed logical verbal memory.…”
Section: Methodsmentioning
confidence: 99%
“…The subjects who completed the short form after the full administration were familiar with all the selected subtests, but lacked familiarity with most subtests when the order of administration was reversed. Matarazzo and Herman (1984) reported Full Scale IQ gains of 6.2 IQ points for adults retested over 2 to 7 weeks with the WAIS-R. Thompson and Molly (1993) found that 16-yearolds retested after 3 months with the full WAIS-R gained 7 Full Scale IQ points. The 1 1-point gain by subjects of this study retested with SF4 an average of 2 months after the Full Scale was probably the result of practice combined with other factors that contribute to the less than perfect correspondence between the abbreviated and full measure.…”
Section: Discussionmentioning
confidence: 99%